2000
DOI: 10.1046/j.1365-2141.2000.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for mutations of Bcl10 in leukaemia

Abstract: The Bcl10 gene was identified through characterization of the t(1;14)(p22;q32) associated with mucosa‐associated lymphoid tissue (MALT) lymphoma. Bcl10 is implicated in the regulation of apoptosis and has been reported to be mutated in other subtypes of non‐Hodgkin's B‐cell lymphoma (B‐NHL) and leukaemic cell lines, raising the possibility that its deregulation could be implicated in other forms of haematological malignancy. We screened 226 cases, including 123 acute myeloid leukaemia (AML), 50 acute lymphobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[1][2][3] We analyzed a series of gastric MALT-type lymphomas for the occurrence of BCL10 mutations. We detected 3 commonly reported polymorphisms [3][4][5]12 that occurred 12 times in 11 cases (1, 7, and 4 times, respectively, in codons 5, 8, and 213). The polymorphic nature of codon 8 and 213 alterations was further confirmed by the analysis of reactive tissues and matched normal cells of the lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] We analyzed a series of gastric MALT-type lymphomas for the occurrence of BCL10 mutations. We detected 3 commonly reported polymorphisms [3][4][5]12 that occurred 12 times in 11 cases (1, 7, and 4 times, respectively, in codons 5, 8, and 213). The polymorphic nature of codon 8 and 213 alterations was further confirmed by the analysis of reactive tissues and matched normal cells of the lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…The substitution in codon 5 was G to T (GCA Ͼ TCA) (exon 1), causing an amino acid substitution (ALA Ͼ SER) and was previously described by others as a polymorphism. 4,5,12 Analysis on DNA derived from microdissected tumor cell clusters revealed 2 additional differences with the published BCL10 sequence, both single nucleotide substitutions. One of these was found in a tumor cell cluster of case 13.…”
Section: Bcl10 Gene Mutationmentioning
confidence: 93%
See 2 more Smart Citations
“…The appearance of this splice variant in the tumors but not in the reactive tonsils initially suggested its tumorigenetic role, as proposed in the early publications. 1 However, it has also been reported that this splice variant is present in bone marrow specimens from normal individuals, 8 so it seems likely that the splice variant might be a response to an altered cellular state in the tumor. In case 14, the variant-promoting mutation could be a tumorigenic event.…”
mentioning
confidence: 99%